Anomalous origin of left pulmonary artery from the ascending aorta: echocardiography assessment. (16th December 2019) - Atmani, Samir; Bendris, Imane
Abstract: Anomalous origin of one pulmonary artery from the ascending aorta is a rare cardiac anomaly in which the pulmonary artery abnormally arises from the ascending aorta. Physiologically, most patients develop signs of cardiac failure due to high flow to both lungs. The purpose of this study is to demonstrate, with this rare anomaly, the accurate place of the echocardiography to establish diagnosis especially in the systemic or supra-systemic pulmonary hypertension.